Current status and influencing factors of test anxiety of senior one students in Yanji, China: a cross-sectional study - Xing, Xin-Yang; Wang, Gui-Meng; Li, Ying; Zhang, Wen-Xuan; Shen, Xiang-Dan (Frontiers in Psychology, 2024)
Objective Examining the current situation of test anxiety among first year senior high school students in Yanji City and investigating the factors that contribute to exam anxiety. Methods Using cluster sampling, a survey was conducted on 1550 first-year high school students from three high schools in Yanji City in April-May 2023. The survey utilized general information questionnaires, the Minnesota Multiphasic Personality Inventory (MMPI), and the Self-Rating Anxiety Scale (SAS). Logistic regression analysis was used to determine the influencing factors of test anxiety. Results A total of 1550 first-year high school students were included in the analysis, with a test anxiety occurrence rate of 79.8%. Test anxiety exhibited statistical differences among different genders, ethnicities, family economic levels, frequency of communication with parents, and relationships with parents (with results of 53.44, 10.42, 17.31, 20.42, 31.95, all P<0.05). Scores of hypochondriasis (Hs), depression (D), psychasthenia (Pt), paranoia (Pa), psychopathic deviate (Pd), schizophrenia (Sc), and hypomania (Ma) in the 10 clinical personality scales were significantly positively correlated. Logistic regression analysis revealed that gender, ethnicity, frequency of communication with parents, and scores of hypochondriasis (Hs), depression (D), psychasthenia (Pt), paranoia (Pa), and hypomania (Ma) in the 10 clinical personality scales were the main influencing factors for test anxiety in first-year high school students (all P<0.05). Conclusion The test anxiety level of high school students in Yanji City is relatively high, with variations in test anxiety levels among students of different genders, ethnicities, parental communication styles, and deviant personality traits. It is recommended that schools and teachers should give more consideration to test anxiety among high school students, particularly targeting those with potential risk factors. Parents should also be more attentive to their children's development and advancement, and improve their family education principles.